EVALUATION OF THE EFFECTS OF THE HYDRO-ETHANOLIC ROOT EXTRACT OF ZANTHOXYLUM ZANTHOXYLOIDES ON HEMATOLOGICAL PARAMETERS AND OXIDATIVE STRESS IN CYCLOPHOSPAMIDE TREATED RATS - Ikumawoyi, V.O.; Awodele, O.; Rotimi, K.; Fashina, Y.A. (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: The use of cyclophosphamide in cancer therapy is usually associated with challenging immunosuppression which exposes patients to increased risk of anemia and necessitating preventive measures during therapy. This study was carried out to investigate the efficacy of the hydro-ethanolic extract of the root of Z. zanthoxyloides in preventing and/or improving cyclophosphamide induced myelosuppression and oxidative stress in rats. Materials and Methods: Animals were divided into 6 groups of 6 rats each and were pretreated oral doses of 75, 150 and 225 mg/kg of the extract for 7 days and then co-administered with 2.5 mg/kg cyclophosphamide for 28 days. Results: The LD50 of the extract was found to be 1682.3 mg/kg. Phytochemical analysis of the plant extract showed the presence of tannins, saponins, alkaloids and flavonoids, glycosides, terpenoids and phenols. In the anti-oxidant enzyme assay, CAT was significantly (p < 0.05) increased for animals treated with 150 mg/kg+CP compared to 75 mg/kg+CP and 225 mg/kg+CP. GPx was significantly (p < 0.01) increased in rats treated with 75 mg/kg+CP compared to 150 mg/kg+CP and control. SOD was significantly (p < 0.01) increased in rats treated with 75 mg/kg+CP compared to the control. WBC was significantly (p < 0.05) reduced for 225 mg/kg, 225 mg/kg+CP (p < 0.001), 150 mg/kg+CP (p < 0.001), 75 mg/kg+CP (p < 0.001) and CP administered rats (p < 0.001) respectively compared to the control. LDL and CHOL were significantly reduced (p < 0.05) for rats treated with 75 mg/kg+CP, 225 mg/kg+CP and 225 mg/kg. Conclusion: Findings from this study demonstrates that the hydro-ethanolic root extract of Z. zanthoxyloides could be beneficial in hyperlipidemia and in cases of malignancies with abnormal cholesterol metabolism an effect which may be mediated via combating oxidative stress.